2012
DOI: 10.1007/s10686-012-9324-z
|View full text |Cite
|
Sign up to set email alerts
|

Corner-cube retro-reflector instrument for advanced lunar laser ranging

Abstract: Lunar laser ranging (LLR) has made major contributions to our understanding of the Moon's internal structure and the dynamics of the Earth-Moon system. Because of the recent improvements of the ground-based laser ranging facilities, the present LLR measurement accuracy is limited by the retro-reflectors currently on the lunar surface, which are arrays of small corner-cubes. Because of lunar librations, the surfaces of these arrays do not, in general, point directly at the Earth. This effect results in a spread… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…It is recommended that the new radio telescope is colocated with a retroreflector, either a panel of cornercubes (Vasiliev et al 2014), or a next generation single cube retroreflector (Turyshev et al 2013;Araki et al 2016). Requiring no power on the Moon and no data transmission, the Earth-Moon laser ranging would help to determine the precise location of the station, and also independently contribute to study of lunar dynamics, and building of the lunar reference frame, and testing general relativity (Murphy 2013;Williams et al 2013b;Pavlov et al 2016;Viswanathan et al 2018).…”
Section: Co-locationmentioning
confidence: 99%
“…It is recommended that the new radio telescope is colocated with a retroreflector, either a panel of cornercubes (Vasiliev et al 2014), or a next generation single cube retroreflector (Turyshev et al 2013;Araki et al 2016). Requiring no power on the Moon and no data transmission, the Earth-Moon laser ranging would help to determine the precise location of the station, and also independently contribute to study of lunar dynamics, and building of the lunar reference frame, and testing general relativity (Murphy 2013;Williams et al 2013b;Pavlov et al 2016;Viswanathan et al 2018).…”
Section: Co-locationmentioning
confidence: 99%
“…html). Therefore, especially for the investigation of the lunar rotational variations, increasing normal point data from retroreflectors as far as possible from the A15 site (Turyshev et al 2013) is an important goal, in addition to the goal of increasing the range accuracy. Further, it is reported that the reflectivity of lunar reflectors shows degradation by a factor of 10 or more (Murphy et al 2010), which may affect data accuracy and productivity.…”
Section: Llr and Retroreflector On The Moonmentioning
confidence: 99%
“…1). As for the reflection performance, the ray path difference in the A15 retroreflector is already ±7 cm [±1 (m) sin 8.2°] due to the array configuration and the optical (lunar orbital) libration, which is the main factor that limits range accuracy and peak value of returned pulse through the broadening of output laser pulse (Turyshev et al 2013). "Single-element retroreflector" (SERR) composed of a single corner-cube reflector made of a prism or three mirrors, which has no optical path difference in principle, is considered a solution to overcome these problems.…”
Section: Conceptual Design Of New Retroreflectormentioning
confidence: 99%
“…LSEI plans to use Single Cube Retroreflectors (SCR) as Laser ranging targets [29] for navigation during deployment of the LSE and the Landing Platform. The SCR would become a permanent addition to the Lunar Laser Ranging (LLR) retroreflector network.…”
Section: The Prototype Lunar Space Elevator Infrastructurementioning
confidence: 99%